2021
DOI: 10.1002/eqe.3575
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality reduction of the 3D inverted pendulum cylindrical oscillator and applications on sustainable seismic design of bridges

Abstract: The simplest 3D extension of Housner's planar rocking model is a rocking (wobbling) cylinder allowed to uplift and roll on its circumference, but constrained not to roll out of its initial position. The model is useful for the description of bridges that use rocking as a seismic isolation technique, in an effort to save material by reducing the design moment and the size of the foundations. This paper shows that describing wobbling motion in terms of displacements rather than rotations is more useful. It unvei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 82 publications
(155 reference statements)
0
12
0
Order By: Relevance
“…However, a coupled analysis is allowed when modeling the contents and the buildings in an integrated manner in OpenSees. Note also that the three‐dimensional (3D) behavior of rocking contents is considerably more complicated, 44 and 3D rocking oscillators 45 could be used when dealing with these more general 3D loading scenarios.…”
Section: Modeling Of Freestanding Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a coupled analysis is allowed when modeling the contents and the buildings in an integrated manner in OpenSees. Note also that the three‐dimensional (3D) behavior of rocking contents is considerably more complicated, 44 and 3D rocking oscillators 45 could be used when dealing with these more general 3D loading scenarios.…”
Section: Modeling Of Freestanding Contentsmentioning
confidence: 99%
“…However, a coupled analysis is allowed when modeling the contents and the buildings in an integrated manner in OpenSees. Note 5 Comparison of the acceleration spectra of the selected ground motions recommended by the FEMA P-695 report 47 with the code-specified MCE spectrum according to GB50011-2010 48 also that the three-dimensional (3D) behavior of rocking contents is considerably more complicated, 44 and 3D rocking oscillators 45 could be used when dealing with these more general 3D loading scenarios.…”
Section: Modeling Of Freestanding Contentsmentioning
confidence: 99%
“…[ 75–77 ] concluded that PGV performs overall better than PGA. Vassiliou and Sieber [ 78 ] studied 3D rocking and concluded that the displacement response scales with a bivariate intensity measure that includes both PGA and PGV.…”
Section: Introductionmentioning
confidence: 99%
“…Studying free and restrained rocking systems of negative systems under sets of far-field, near-field pulse-like and near-field non-pulse-like ground motions, Manzo et al [75][76][77] concluded that PGV performs overall better than PGA. Vassiliou and Sieber [78] studied 3D rocking and concluded that the displacement response scales with a bivariate intensity measure that includes both PGA and PGV.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it finds application on a variety of engineering projects, e.g. from freestanding contents [22,39,40] and classical monuments [23,49,63] to modern buildings and bridges [2,18,21,26,28,54,[59][60][61]. From an earthquake engineering perspective, the transient response of a rocking structure under a finite duration ground excitation is of primary importance, as it directly relates to seismic safety and structural failure [15,19,45,55,56,62].…”
Section: Introductionmentioning
confidence: 99%